2021
DOI: 10.1038/s41598-021-86658-5
|View full text |Cite
|
Sign up to set email alerts
|

In oxygen-deprived tumor cells ERp57 provides radioprotection and ensures proliferation via c-Myc, PLK1 and the AKT pathway

Abstract: The disulfide isomerase ERp57, originally found in the endoplasmic reticulum, is located in multiple cellular compartments, participates in diverse cell functions and interacts with a huge network of binding partners. It was recently suggested as an attractive new target for cancer therapy due to its critical role in tumor cell proliferation. Since a major bottleneck in cancer treatment is the occurrence of hypoxic areas in solid tumors, the role of ERp57 in cell growth was tested under oxygen depletion in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Nuclear VDR is a type of nuclear hormone receptor, and most of the biological actions are mediated through the VDR-mediated control of target genes [ 47 ]. Pdia3 is a pleiotropic, ER-resident protein that has been detected on the cell surface [ 48 ], in the cytoplasm [ 49 ], and in mitochondria [ 50 ]. Pdia3 is located in cellular compartments other than the ER and is involved in a variety of cellular functions such as signal transduction, protein trafficking, interacting with mTOR, and regulation of STAT3 signaling [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear VDR is a type of nuclear hormone receptor, and most of the biological actions are mediated through the VDR-mediated control of target genes [ 47 ]. Pdia3 is a pleiotropic, ER-resident protein that has been detected on the cell surface [ 48 ], in the cytoplasm [ 49 ], and in mitochondria [ 50 ]. Pdia3 is located in cellular compartments other than the ER and is involved in a variety of cellular functions such as signal transduction, protein trafficking, interacting with mTOR, and regulation of STAT3 signaling [ 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…PLK1 is known to play an important role in initiating, completing, and maintaining the cell mitotic cycle 25 . Elevated levels of PLK1 transcription, or protein expression, have been found in a variety of human solid tumors, including lung, breast, stomach, cervical, and colon cancers 26 . Multiple studies have shown that PLK1/ERK is a key pathway to induce malignant transformation and tumor formation of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following the KEGG signal pathway analysis, the mechanisms of CP in the treatment of HUA mainly involved inflammation and apoptosis signaling pathways, including PI3K/Akt, TNF, FoxO, MAPK, HIF-1, TLR, NLRP3, AMPK, and NF-κB. The PI3K/Akt pathway is a crucial pathway that regulates cell proliferation, cell survival, cell cycle progression, and cancer metabolism (Ocklenburg et al, 2021). Studies have found that in the Uox-knock-out-induced HUA and nephropathy rat line, the PI3K inhibitor 3-MA alleviates kidney injury accompanied by renal fibrosis, macrophage infiltration, and expression of NLRP3 and IL-1β in injured kidneys (Wu et al, 2021).…”
Section: Figurementioning
confidence: 99%